Diabetes, heart failure, and renal dysfunction: The vicious circles - Braunwald, Eugene (Progress in cardiovascular diseases, 2019)
The prevalence of Type 2 diabetes mellitus (T2DM) has reached pandemic proportions. T2DM frequently causes macrovascular and/or microvascular pathologic changes and thereby increases the risks for the development of myocardial infarction, heart failure, stroke, renal failure, and reduced survival. This article describes the important interactions between T2DM, heart failure, and renal dysfunction, forming vicious circles. The interruption of these circles represents important therapeutic goals.